2016
DOI: 10.1210/jc.2016-2032
|View full text |Cite
|
Sign up to set email alerts
|

Combined Oral Contraceptives and Sexual Function in Women—a Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: This study shows no negative impact of a levonorgestrel-containing oral contraceptive on overall sexual function, although three of seven sexual function domains were adversely affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 31 publications
11
52
2
2
Order By: Relevance
“…In a recent paper based on the same clinical trial as here, we found evidence of negative effects of this OC on general well-being (Zethraeus et al 2017), and on sexual well-being for some of our secondary outcome measures but not our primary outcome measure (Zethraeus et al 2016). Thus, even though this OC does not appear to affect economic preferences, there is evidence of other effects of this OC using the same setup as here.…”
Section: Discussionsupporting
confidence: 64%
“…In a recent paper based on the same clinical trial as here, we found evidence of negative effects of this OC on general well-being (Zethraeus et al 2017), and on sexual well-being for some of our secondary outcome measures but not our primary outcome measure (Zethraeus et al 2016). Thus, even though this OC does not appear to affect economic preferences, there is evidence of other effects of this OC using the same setup as here.…”
Section: Discussionsupporting
confidence: 64%
“…This is a sub‐study of a large randomized placebo controlled study including 340 healthy women, 18 to 35 years of age, body mass index 19–30, with regular menstrual cycles (25–33 days) . One hundred sixty‐nine women were assigned to three months’ treatment with combined monophasic oral contraceptive (OC) Neovletta ® , a Bayer Schering Pharma containing 150 μg of levonorgestrel and 30 μg of ethinylestradiol.…”
Section: Methodsmentioning
confidence: 99%
“…Specific gravity was measured using a Digital Urine SG Refractometer (ATAGO UG1, Tokyo, Japan) to adjust for different urine dilutions. Serum steroid analyses of testosterone and gonadotropins (FSH and LH) have previously been determined with liquid chromatography–tandem mass spectrometry (LC–MS/MS) and fluorescence immunoassays, respectively …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations